Measurement and quality control of process and products in manufacturing and enterprise - Stępień, Krzysztof (Key engineering materials, 2015)
International Symposium on Measurement and Quality Control (ISMQC) is one of the most important scientific events that is normally held once in every three years in the field of measurements and quality control. During ISMQC 2013 that were selected by Programme Committee to be published in the Special Issue of ""Key Engineering Materials"" and one additional paper whose subject fits perfectly the scope of the symposium